Ruthenium Oxidation Complexes Their Uses as Homogenous Organic Catalysts - Griffith, William P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Ruthenium Oxidation Complexes explores ruthenium complexes, particularly those in higher oxidation states, which function as useful and selective organic oxidation catalysts. Particular emphasis is placed on those systems which are of industrial significance. The preparation, properties and applications of the ruthenium complexes are described, followed by a presentation of their oxidative properties and summary of the different mechanisms involved in the organic oxidations (e.g. oxidations of alcohols, alkenes, arenes and alkynes, alkanes, amines, ethers, phopshines and miscellaneous substrates). Moreover, future trends and developments in the area are discussed. This monograph is aimed at inorganic, organic, industrial and catalysis chemists, especially those who wish to carry out specific organic oxidations using catalytic methods.
1. Introduction -- 2. Oxidation of Alcohols, Carbohydrates, Diols and Polyols -- 3. Oxidation of Alkenes, Arenes and Alkynes -- 4. Oxidation of Alkanes -- 5. Oxidations of Amines, Amides, Ethers, Sulfides, Phosphines, Arsines, Stibines and Miscellaneous Substrates.
Keywords: Chemistry; Chemistry, inorganic; Chemistry, Organic; Chemical engineering; Catalysis; Chemistry; Organic Chemistry; Catalysis; Inorganic Chemistry; Industrial Chemistry/Chemical Engineering